1985
DOI: 10.1017/s002237780000235x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear propagation and localization of intense electromagnetic waves in relativistic plasmas

Abstract: An analytical formulation is presented for envelope-type solutions of intense polarized electromagnetic waves propagating in cold unmagnetized plasmas. Induced charge separation is fully taken into account and nonlinearities due to mass variation of both electrons and ions are included. Localized solutions are found for the case of subluminous wave phase velocity. The spectrum of solutions (dependence of wave amplitude on the free parameters in the theory, phase velocity and frequency) is discussed and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…(7) and (8) casts itself into the convenient format we were looking for. If the transverse structure is neglected, the set becomes similar to models analyzed in the past (Mofiz & de Angelis, 1985). Under this planar condition, one can think of Eqs.…”
Section: Governing Equation In the Weakly Nonlinear Approximationmentioning
confidence: 99%
“…(7) and (8) casts itself into the convenient format we were looking for. If the transverse structure is neglected, the set becomes similar to models analyzed in the past (Mofiz & de Angelis, 1985). Under this planar condition, one can think of Eqs.…”
Section: Governing Equation In the Weakly Nonlinear Approximationmentioning
confidence: 99%
“…V could be thus read as a nonlinear group velocity since we shall be working in regimes where ω and k are related by a nonlinear dispersion relation. Manipulation of the governing equations finally takes us to the point where two coupled equations must be integrated -one controlling the vector potential, and the other the electric potential [7,8]:…”
Section: The Modelmentioning
confidence: 99%
“…Since it can be shown that the electronic density depends on r e in the form n e ∼ r −1 e [7,8], break down of the theory indicates wave breaking on electrons. Also shown in the figure is the wave breaking energy…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(Kozlov et al, 1979;Tajima & Dawson, 1979;Mofiz & de Angelis, 1985;Shukla et al, 1986;Esarey et al, 1998;Farina & Bulanov, 2001;Mendonça, 2001;Poornakala et al, 2002;Bingham, 2003;Joshi & Katsouleas, 2003).…”
Section: Introductionmentioning
confidence: 99%